2020 Asian Pacific Society of Cardiology Consensus Recommendations on the Use of P2Y12 Receptor Antagonists in the Asia-Pacific Region - Jack WC Tan; Derek P Chew; Muhamad Ali SK Abdul Kader; Junya Ako; Vinay K Bahl; Mark Chan; Kyung Woo Park; Praveen Chandra; I-Chang Hsieh; Do Quang Huan; Sofian Johar; Dafsah Arifa Juzar; et al. (European Cardiology Review)
The unique characteristics of patients with acute coronary syndrome in the Asia-Pacific region mean that international guidelines on the use of dual antiplatelet therapy (DAPT) cannot be routinely applied to these populations. Newer generation P2Y12 inhibitors (i.e. ticagrelor and prasugrel) have demonstrated improved clinical outcomes compared with clopidogrel. However, low numbers of Asian patients participated in pivotal studies and few regional studies comparing DAPTs have been conducted. This article aims to summarise current evidence on the use of newer generation P2Y12 inhibitors in Asian patients with acute coronary syndrome and provide recommendations to assist clinicians, especially cardiologists, in selecting a DAPT regimen. Guidance is provided on the management of ischaemic and bleeding risks, including duration of therapy, switching strategies and the management of patients with ST-elevation and non-ST-elevation MI or those requiring surgery. In particular, the need for an individualised DAPT regimen and considerations relating to switching, de-escalating, stopping or continuing DAPT beyond 12 months are discussed.